Fuzzy Quotient-3 Cordial Labeling of Generalized Jahangir Graph and its Subdivision Graph - Dr.P. Sumathi, J.Suresh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Let the functionσ : V → [0,1] defined by σ(ϑ) = γ 10 , γ ∈ Z4 − {0}is called the fuzzy quotient-3 cordiallabeling if for each edgesωϑ ∈